Zones of maximum discontinuity in the western house mouse (M. m. domesticus) genetic landscape: a computational geometry method. - Zarei, Fatah; Hussein, Ridha H. (Sulaimani Journal for Pure and Applied Sciences, 2016)
To represent the zones of maximum genetic discontinuity in a network of geographically located populations of western house mouse from the previously published mitochondrial DNA D-loop sequence datasets which we acquired from the NCBI GenBank database, we applied a computational geometry approach using the Monmonier’s maximum difference algorithm implemented in the BARRIER 2.2 software. We defined ten zones where genetic change among populations is locally increased, three of them occur within the Middle East, while seven occur in Europe. Analysis of molecular variance among post-hoc defined regions using the pattern generated by the BARRIER analysis showed that a significant portion of the genetic diversity was because of among groups component.
Keywords: BARRIER analysisGenetic discontinuityMonmoniers algorithmWestern house mouse